Kualitas Petis Daging dengan Level Gula Jawa dan Tepung Beras yang Berbeda - Agus Susilo; Masdiana Chendrakasih Padaga; Fani Yunita Pratiwi (Jurnal Ilmu dan Teknologi Hasil Ternak (JITEK), 2016)
The aimed of this study was to determine quality of meat paste from different level rice Â starch and java sugar based on from physical, chemical and sensory test. The experiment used was Factorial Randomized Block design. Meat paste make from different level rice starch and java sugar. Starch properties content, protein content, viscosity and sensory test has evaluated from meat paste. Amino acid profiles was analysedÂ  from the best result the experiment. Rice starch and the java sugar has significantly influenced the quality of meat paste. They gave a highly significant effect on the viscosity, flavour, colour and taste.